Analisis Nilai dan Kualitas Ruang Menggunakan Pendekatan Kriteria Tak Terukur pada Kawasan Kampung Batik Kauman sebagai Kawasan Wisata Budaya Kota Pekalongan - Nofa Martina Ariani; Muhammad Indra Hadi Wijaya; Bagus Nuari Priambudi (JURNAL LITBANG KOTA PEKALONGAN, 2021)
Pekalongan City is one of the cities with a batik cultural heritage preserved from tens or even hundreds of years ago. Most of the batik has been done by the community at home. Batik work, which has become the community's livelihood, slowly forms the peculiarities of regional spaces that can give an impression to visitors. This can be felt in an area known as Kampung Batik, one of which is Kampung Batik Kauman. Kauman Batik Village has now transformed into one of the cultural tourism destinations offered by the Pekalongan City Government. The uniqueness of the city space which is thick with culture and community activities is an attraction that is considered capable of providing tourist experiences and education related to batik production. This study analyzes the spatial area in Kampung Batik Kauman by using an unmeasured criteria analysis approach as a strong supporter to give an impression to observers. The results of the analysis show that Kampung Batik Kauman has met 6 (six) indicators of the unmeasured criteria although it needs improvement in several parts. The most powerful indicators are access, identity, and livability. The description of this analysis can be used as input for t he Pekalongan City Government to increase its attractiveness and at the same time foster a love for urban space that has history and culture. Keyword: Kampung batik, cultural heritage, unmeasured criteria